Genomics in neglected and underutilized fruit crops: A chromosome‐scale genome sequence of cherimoya (Annona cherimola). Issue 3 (21st February 2023) - Talavera, Alicia; Fernandez‐Pozo, Noe; Matas, Antonio J.; Hormaza, Jose I.; Bombarely, Aureliano
Abstract : Societal Impact Statement: Cherimoya has been an important food source since Pre‐Columbian times in the Americas. Although it is currently considered an underutilized fruit crop, it is still important at the local level in several regions of Central and South America, and has a clear niche for expansion in regions with subtropical climates. However, the availability of genomic resources to facilitate breeding programs and improve the understanding of Annonaceae genetic diversity is limited. In this work, we provide an important resource to fill this knowledge gap, with the hope that it will ultimately increase this crop's resilience under different climate change scenarios, which will increase food security in regions with subtropical climates. Summary: Cherimoya ( Annona cherimola Mill.) is a perennial fruit tree crop native to the Neotropics valued since pre‐Columbian times by different native American civilizations. It belongs to the Annonaceae, the largest family of the Magnoliid clade, sister to the eudicot and monocot clades of angiosperms. Despite its excellent organoleptic and nutritive qualities, this crop remains underutilized, although it has a clear niche for expansion in regions with subtropical climates. To date, no previous significant genomic information is available for this species, which would be a key tool to optimize breeding programs and advance in the study and conservation of its extant genetic diversity. A combination of different sequencing technologies (Illumina, Pacific Biosciences) has been implemented in order to assemble a chromosome‐level reference genome of A. cherimola . The final reference genome resulted in an assembly of 1.13 Gb and N50 of 170.86 Mb, anchored into seven pseudomolecules and with a completeness of 95.6%. A total of 41, 413 protein‐coding genes were identified, many of which were related to secondary metabolism, defense mechanisms, stress response, and development. The results of this study provide novel significant genomic resources not only for cherimoya and other species of the Annonaceae but also for understanding the evolution of the earlier divergent angiosperms. Abstract : Cherimoya has been an important food source since Pre‐Columbian times in the Americas. Although it is currently considered an underutilized fruit crop, it is still important at the local level in several regions of Central and South America, and has a clear niche for expansion in regions with subtropical climates. However, the availability of genomic resources to facilitate breeding programs and improve the understanding of Annonaceae genetic diversity is limited. In this work, we provide an important resource to fill this knowledge gap, with the hope that it will ultimately increase this crop's resilience under different climate change scenarios, which will increase food security in regions with subtropical climates. Alternative language Societal Impact Statements: El chirimoyo ha sido muy apreciado como alimento desde tiempos precolombinos por diferentes culturas de las Américas. Es actualmente considerado un cultivo infrautilizado, aunque es importante a nivel local en diferentes países de Centro y Sudamérica, y tiene un claro nicho de expansión en regiones subtropicales. Sin embargo, la disponibilidad de recursos genómicos para facilitar los programas de mejora e incrementar el conocimiento de la diversidad genética de las Annonaceae es limitada. En este trabajo proporcionamos un importante recurso con el fin de reducir esta brecha, con la esperanza de que en última instancia permita una mejor adaptación de este cultivo a los desafíos planteados por el cambio climático y, por tanto, facilite la seguridad alimentaria en regiones subtropicales.